Деградация структуры и свойств металла рельсов при длительной эксплуатации; Успехи физики металлов; Т. 17, № 3 - Громов В. Е. Виктор Евгеньевич; Иванов Ю. Ф. Юрий Федорович; Перегудов О. Олег; Морозов К. В. Константин Викторович; Семин А. П. Александр Петрович (2016, 2016)
Заглавие с экрана